Use of lung ultrasound in the differential diagnosis of the causes of dyspnea - Bulatović, Kristina; Ristic - Andjelkov, Andjelka; Perić, Vladan; Todorović, Jovana; Pandrc, Milena; Gojka, Gabrijela; Vraneš, Danijela; Šipić, Maja; Rašić, Dragiša; Milenković, Aleksandra; Aritonović Pribaković, Jelena; Perić, Milica (Vojnosanitetski pregled, 2023)
Background/Aim. The field of lung ultrasonography (US) is a fast-developing one, and it provides the medical community with numerous new diagnostic opportunities. The aim of this study was to examine the etiology of dyspnea on admission and assess the stage of heart failure (HF) according to the US examination of the heart and lungs. Methods. The cross-sectional study included a total of 110 patients treated for the symptoms of dyspnea. The study included all patients treated for any heart or pulmonary condition, as well as patients who reported the first episode of dyspnea without any previous illness. The most important diagnostic sign in the US of the lungs in patients with HF was the appearance of B-lines or “comets” (ultrasound artifacts reminiscent of comet tails), which indicate the accumulation of fluid in the interstitium of the lungs. Results. The mean number of registered “comets” in the total number of patients was 14.2 ± 7.4 (minimum 2, maximum 30). The mean number of “comets” among patients with HF was 18.8 ± 5.9. The mean number of “comets” among patients without HF was 8.0 ± 3.7 (p ˂ 0.001). Multivariate linear regression analyses showed the association between the number of “comets” and HF (p ˂ 0.001). Conclusion. As the assessment of present “comets” in pulmonary US examination is safe and non-invasive, it can easily be integrated into the daily clinical practice because it has been shown that the number of pulmonary “comets” is significantly higher in patients with HF compared to those with dyspnea of ​​other etiologies.
Keywords: diagnosis, differential; dyspnea; heart failure; pulmonary edema; ultrasonography